How do you find the derivative of #y=6sin(2t) + cos(4t)#?

3 Answers
Jun 10, 2018

Answer:

#y'=12cos(2t)-4sin(4t)#

Explanation:

Using that

#(sin(x))'=cos(x)#
#(cos(x))'=-sin(x)#
and
#(u+v)'=u'+v'#
and the chain rule we get

#y'=6cos(2t)*2-sin(4t)*4#
so
#y'=12cos(2t)-4sin(4t)#

Jun 10, 2018

Answer:

#y'=4(3cos(2t)-sin(4t))#

Explanation:

enter image source here
Let me know if you need clarification on any steps.

Jun 10, 2018

Answer:

#color(blue)(y' = 4 * (3 cos 2t - sin 4t)#

Explanation:

#y = 6 sin 2t + cos 4t#

https://www.pinterest.co.uk/pin/527413806338349072/

Applying the Chain rule,

#y' = 6 * d(sin (2t)) + d (cos (4t))#

#y' = 6 cos 2t * d(2t) - sin 4t * d(4t)#

#y' = 6 * cos 2t * 2 - sin 4t * 4#

#y' = 12 cos 2t - 4 sin 4t#

#color(blue)(y' = 4 * (3 cos 2t - sin 4t)#